A Comparison of Published Accounting Research and Qualities of Accounting Faculty and Doctoral Programs. - Bazley, John D.; Nikolai, Loren A.; De Coster, Don T. (The Accounting Review, 1975)
This article presents a study conducted to compare published accounting research and qualities of accounting faculty and doctoral programs. Recently, two studies have been published in which accounting departments were ranked according to some perceived criterion of excellence. Neither of these studies described the criterion of excellence to be utilized in the development of the rankings; rather they allowed the respondents to use their own subjective criteria. Objective criteria would be preferable as a basis for assessing the quality of the various accounting departments. One such criterion is the amount of research which is attributable to each department, and an indicator of research output is the number of articles published in the accounting journals. The results of this study are subject to several limitations. The study only analyzed the research which has been published in four accounting journals, one of which is published by the University of Chicago. No attempt was made to evaluate the effect of differences in the sizes of accounting faculties or doctoral programs.